1997
DOI: 10.1016/s0014-5793(97)00343-8
|View full text |Cite
|
Sign up to set email alerts
|

Production of formyl‐CoA during peroxisomal α‐oxidation of 3‐methyl‐branched fatty acids

Abstract: a-Oxidation of 3-methyl-substituted fatty acids was studied in purified rat liver peroxisomes. The experiments revealed that formyl-CoA is formed during the a-oxidation process. The amount of formyl-CoA found constituted 2-5% of the amount of formate formed. Under the conditions used, no activation of exogenously added formate occurred in purified peroxisomes, whereas 95.5% of added synthetic formyl-CoA was converted to formate. These data indicate that during aoxidation first formyl-CoA is formed, which is th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 18 publications
(29 reference statements)
0
35
1
Order By: Relevance
“…Originally, it was presumed that CO 2 was produced in this reaction, but this hypothesis was refuted by Poulos et al [31], who observed that > 90% of the radioactivity coming from [1-14 C]phytanic acid α-oxidation in fibroblasts was present in the water-soluble, instead of the gaseous fraction. They and others [28] showed that the radioactivity came from formate, or, rather, as was discovered somewhat later, from formyl-CoA, which is now known to be the true product of the decarboxylation of phytanic acid [32] ( Fig. 2b).…”
Section: Decarboxylation Of Phytanic Acidmentioning
confidence: 88%
“…Originally, it was presumed that CO 2 was produced in this reaction, but this hypothesis was refuted by Poulos et al [31], who observed that > 90% of the radioactivity coming from [1-14 C]phytanic acid α-oxidation in fibroblasts was present in the water-soluble, instead of the gaseous fraction. They and others [28] showed that the radioactivity came from formate, or, rather, as was discovered somewhat later, from formyl-CoA, which is now known to be the true product of the decarboxylation of phytanic acid [32] ( Fig. 2b).…”
Section: Decarboxylation Of Phytanic Acidmentioning
confidence: 88%
“…Phytanoyl-CoA is then imported into peroxisomes followed by ␣-oxidation, which involves hydroxylation at the ␣-carbon position by phytanoyl-CoA hydroxylase (PHYH). Subsequently, 2-OH-phytanoyl-CoA is converted to pristanic acid and formyl-CoA (Wanders et al 1994;Croes et al 1997). Whereas formyl-CoA is further catabolized in mitochondria, pristanic acid is activated to pristanoylCoA, which is then subject to six cycles of peroxisomal ␤-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…(4). Reactions were terminated after 10 min with 125 l 6% (wt͞vol) HClO 4 , and the acidified mixtures were used for the measurement of radioactive formate (22).…”
Section: Preparation Of Homogenates and Subcellular Fractionsmentioning
confidence: 99%
“…Other incubations were terminated by adding 50 l of 1 M K-phosphate, pH 2, and [ 14 C]formate and [1][2][3][4][5][6][7][8][9][10][11][12][13][14] C]formyl-CoA were measured separately by HPLC as described (4). For the analysis of lipid-soluble reaction products, similar incubations with unlabeled 2-hydroxy-3-methylhexadecanoyl-CoA were quenched by adding 0.5 ml of methanol͞glacial acetic acid (98͞2, vol͞vol) and extracted with hexane.…”
Section: Preparation Of Homogenates and Subcellular Fractionsmentioning
confidence: 99%